2004
DOI: 10.1038/modpathol.3800143
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expression of laminin gamma 2 chain and its prognostic significance in intrahepatic cholangiocarcinoma according to growth morphology

Abstract: Laminin gamma 2 chain is an extracellular matrix protein that plays an important role in cell migration and tumor invasion. We report altered expression and characteristic localization of this chain in a series of 105 cases of intrahepatic cholangiocarcinomas examined immunohistochemically. All tumors were grossly classified into the following three types: intraductal growth type (n ¼ 9), periductal infiltrating type (n ¼ 8) and mass-forming type (n ¼ 88). The tumors exhibited three distinct staining types: ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…In most carcinomas, LN-5 γ 2 is expressed in the carcinoma cells at the epithelial-stromal interface in the invasive front [10,11,12,13,14,15,16, 34]. These observations suggest that LN-5 γ 2 has an important role in cancer cell adhesion to the stroma.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In most carcinomas, LN-5 γ 2 is expressed in the carcinoma cells at the epithelial-stromal interface in the invasive front [10,11,12,13,14,15,16, 34]. These observations suggest that LN-5 γ 2 has an important role in cancer cell adhesion to the stroma.…”
Section: Discussionmentioning
confidence: 79%
“…Recent immunohistochemical studies have revealed that the LN-5 γ 2 is strongly expressed in disseminating and infiltrating tumor cells at the invasive front of epithelial carcinomas, and its increased expression in tumor tissues is associated with a poor prognosis [10,14,15,16, 34]. Our results were similar to these observations, and moreover, overexpression of LN-5 γ 2 was shown to be correlated with lymphatic invasion, vascular invasion and the tumor growth pattern in esophageal SCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In invasive intrahepatic cholangiocarcinoma, the stromal accumulation of laminin Á 2 were significantly correlated with tumor aggressive factors and poor prognosis (19). The stromal laminin Á 2 expression is thought to contribute to the tumor cell migration and invasion in a variety of carcinomas (18,19,34).…”
Section: Discussionmentioning
confidence: 99%
“…It is a major component of the basement membrane of various types of epithelial tissue and plays important roles in cell differentiation, adhesion, and migration (14,15 (16,17), gastric (18), intrahepatic cholangial (19), lung (20), breast (16), and pancreatic (21) adenocarcinomas, and head and neck (22), esophageal (23) and uterine cervical (16,17,24) squamous cell carcinomas and malignant melanomas (23). However, the relationship between laminin Á 2 chain expression and ovarian GI-type mucinous neoplasms, including mural nodules, has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%